Experimental Investigations Performance for (VCC) Using 2-Way (PFCV) Type (2FRE) - Oleiwi, Majid Ahmed (Al-Khwarizmi Engineering Journal, 2017)
In modern hydraulic control systems, the trend in hydraulic power applications is to improve efficiency and performance. “Proportional valve” is generally applied to pressure, flow and directional-control valves which continuously convert a variable input signal into a smooth and proportional hydraulic output signal. It creates a variable resistance (orifice) upstream and downstream of a hydraulic actuator, and is meter in/meter out circuit and hence pressure drop, and power losses are inevitable. If velocity (position) feedback is used, flow pattern control is possible. Without aforementioned flow pattern, control is very “loose” and relies on “visual” feed back by the operator. At this point, we should examine how this valve works and how can use it in electro-hydraulic circuit designs. In this paper, constructed and compared velocity control cylinder (VCC) by using a proportional flow control valve (PFCV) and with a fine throttle valve. With the aid of a check valve and that check valve, the proportional valve can be made to act in the “lift” direction, and the fine throttle in the “lower” direction. As with all proportional valves, there is also some hysteresis in a proportional flow control valve. The valve used in this work with a hysteresis of <±1% of . The repetition accuracy is quoted in data sheet as < 1% of . The inferential results are good, acceptable and useful for designers which are working at hydraulic proportional field.